Dysregulation of Podocyte BK Channels and Nephrosis: Effects of Circulating Factors and Auxiliary β4 Subunits - Eun Young Kim; Patrycja Rachubik; Stuart E. Dryer (Cells)
Podocytes express large-conductance Ca2+-activated K+ channels (BK channels) and at least two different pore-forming KCa1.1 subunit C-terminal splice variants, known as VEDEC and EMVYR, along with auxiliary β and γ subunits. Podocyte KCa1.1 subunits interact directly with TRPC6 channels and BK channels become active in response to Ca2+ influx through TRPC6. Here, we confirmed that Ca2+ influx through TRPC channels is reduced following the blockade of BK channels by paxilline. The overall abundance of KCa1.1 subunits, as well as that of β4 and γ3 subunits, were increased in glomeruli isolated from Sprague Dawley rats during chronic puromycin aminonucleoside (PAN) nephrosis. Exposing cultured mouse podocytes for 24 h to recombinant TNFα, a circulating factor implicated in pediatric nephrotic syndromes, did not affect the total abundance of KCa1.1, but did evoke significant increases in both β4 and γ3. However, TNFα evoked a marked increase in the surface abundance of KCa1.1 subunits, similar to that of its previously reported effects on TRPC6 channels. The effect of TNFα on the surface expression of KCa1.1 was eliminated following siRNA knockdown of the β4 subunits, suggesting a role for this subunit in KCa1.1 trafficking to the cell surface. By contrast, treating podocytes with suPAR did not affect the total or surface expression of KCa1.1. The coordinated activation of KCa1.1 channels may promote Ca2+ influx through TRPC channels during normal and abnormal podocyte function by maintaining a membrane potential that allows for the efficient permeation of divalent cations through TRPC pores.